2008
DOI: 10.1002/fam.981
|View full text |Cite
|
Sign up to set email alerts
|

The piloted transition to flaming in smoldering fire retarded and non‐fire retarded polyurethane foam

Abstract: The piloted transition from smoldering to flaming, though a significant fire safety concern, has not been previously extensively studied. Experimental results are presented on the piloted transition from smoldering to flaming in non-fire retarded (NFR) polyurethane foam and the fire retarded polyurethane foam Pyrell ® . The samples are small blocks, vertically placed in the wall of an upward wind tunnel. The free surface is exposed to an oxidizer flow and a radiant heat flux. The smolder product gases pass upw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 26 publications
3
31
0
Order By: Relevance
“…The error in the spread rate is estimated to be ±25% due to the uncertainty of ±2.5 mm in the thermocouple placement in the foam. The spread rates measured for smouldering are in agreement with the work of Anderson et al [5] using a similar experimental set-up but are higher than those generally found for unassisted smouldering [3,17]. The higher spread rate could be explained by the energy assistance provided by the heater.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…The error in the spread rate is estimated to be ±25% due to the uncertainty of ±2.5 mm in the thermocouple placement in the foam. The spread rates measured for smouldering are in agreement with the work of Anderson et al [5] using a similar experimental set-up but are higher than those generally found for unassisted smouldering [3,17]. The higher spread rate could be explained by the energy assistance provided by the heater.…”
supporting
confidence: 89%
“…Putzeys et al [17] found that a minimum heat flux between 8 kW m À2 and 8:75 kW m À2 will result in the transition from smouldering to flaming of a 50 mm 9 50 mm 9 125 mm sample of PU foam with internal forced flow and sample sides heated to 200°C by external means. This value is much lower than that measured here for 50 mm size ð45 kW m À2 to 48 kW m À2 ), but the heating of the samples in [7] sides and the increased air flow dramatically enhance the smouldering combustion, increasing the likelihood of transition to flaming.…”
Section: Transition To Flamingmentioning
confidence: 99%
See 1 more Smart Citation
“…. In comparison, Putzeys et al and Torero and Fernandez-Pello used open cell, non-fire retarded polyurethane foam with density 26.5 kg/m 3 , porosity 0.975 and permeability 2.76•10 −9 m 2 in their experiments on smoldering ignition and propagation[70,84].…”
mentioning
confidence: 99%
“…Flexible polyurethane (PU) foam presents some unique fire threats in the modern home because it is not only a high heat release material when it burns but also because when it burns it collapses into a pool of burning material that can lead to rapid flashover events should beds or upholstered furniture catch fire . Of course, ignition source intensity and the presence/absence of flame retardants (FRs) will affect fire growth from burning PU foam , but even then, most flame retarded flexible foams still drip and flow upon exposure to flame as most of the existing FRs in commercial use for flexible foams are designed to reduce heat release and inhibit ignition and flame spread, not necessarily to prevent dripping . For a FR to be effective in flexible foams, multiple mechanisms of action can be utilized to provide satisfactory performance in a regulatory fire test.…”
Section: Introductionmentioning
confidence: 99%